Palm oil intensification and expansion in Indonesia and Malaysia: Environmental and socio-political factors influencing policy - Varkkey, Helena; Tyson, Adam; Choiruzzad, Shofwan Al Banna (Elsevier, 2018)
Intensification and expansion are two essential tenets of commercial agriculture. This paper analyses trends of intensification and expansion at the national level, particularly in the oil palm sector in Indonesia and Malaysia. Despite similar starting points and also comparable rates of increasing productivity and profit in this sector, both countries have developed almost opposite trajectories of land use. While both intensification and expansion has occurred in these countries, national indicators show that Malaysia has largely pursued intensification while Indonesia has overwhelmingly favoured expansion. Using the framework of the Jevons paradox, this paper contributes to the existing literature by arguing how and why political and social factors, rather than technology and market incentives, can better account for the differences between yield and land use efficiency in Indonesia and Malaysia today. The paper argues that expansion in Malaysia has been curtailed by the Malaysian government's pledge to maintain at least 50% forest cover in the late 1990s, coupled with a government supported corporate strategy of establishing plantations in Indonesia. Indonesia has made no such pledge, leading to expansionist policies focused on market creation and production goals with limited incentives for technology-driven intensification. It also notes however that in recent years, new socio-political developments in both countries may yet change this clear dichotomy of opposing land use strategies between these two countries, namely Sarawak's recent autonomous tendencies over land use and Indonesia's new leadership and international No Deforestation Peat and Exploitation (NDPE) commitments.